Compliance of extended infusion of piperacillin/tazobactam with the desired pharmacokinetic/pharmacodynamic index in septic patients - Tomić Nataša; Vukmirović Saša; Sabo Stanislav; Uvelin Arsen; Popović Radmila; Vicković Sanja; Tomić Ljiljana; Tomić Zdenko (Vojnosanitetski Pregled)
Background/Aim. Piperacillin (PIP)/tazobactam (TAZ) –PIP/TAZ is a beta-lactam antibiotic used to treat Gram-negative sepsis. The portion of the dosing interval during which antibiotic concentrations are above the minimal inhibitory concentration – MIC (fT>MIC) or, even more, four times higher than the MIC (fT>4xMIC), represents the pharmacokinetic indices that best correlate with the clinical outcome. In light of the increasing resistance of bacteria in intensive care units (ICUs), it is important to examine the pharmacokinetic/pharmacodynamic (PK/PD) indices of different PIP/TAZ dosing regimens to determine whether this condition is met. The aim of this study was to analyze the efficacy of prolonged intermittent infusion of PIP/TAZ in patients with sepsis in the ICU to achieve the desired PK/PD index. Methods. A prospective, controlled, non-interventional study included patients with abdominal post-operative sepsis. Patients received PIP/TAZ in a dose of 4.5 g every 6 hrs in an extended (60-min) intermittent infusion in a daily therapeutic dose of 18 g as part of the pre-scribed therapy. Blood samples were collected during the first 36 hrs, and antibiotic concentrations were determined using high-performance liquid chromatography. The analysis included the most common isolates from the blood culture in the ICU that were sensitive to PIP/TAZ, and the MICs were also taken from the European Committee on Antimicrobial Susceptibility Testing (EUCAST) database. The primary objective of the PK/PD study was to determine the indices fT>MIC and fT>4xMIC as the best indicators of therapeutic efficacy. For the pharmacodynamic target, this period was determined to be ≥ 50% of the time of the dosing interval. Results. The maximum achieved PIP concentrations in examined patients were 130.03 ± 32.43 μg/mL. Based on PK/PD data, the applied PIP/TAZ dosing regimen was effective against sensitive strains whose MIC did not exceed 16 μg/mL (fT>MIC = 56%). If we take fT>4xMIC≥50% as a target value, that percentage was significantly below the set goal (27%). For strains that include strains with a phenotypic resistance mechanism, PK/PD values for fT>4xMIC≥50% were far below the set goal (2–11%), except for Escherichia coli (79%). Conclusion. An intermittent 60-min infusion of PIP/TAZ meets the required pharmacodynamic target fT>MIC≥50% for sensitive strains of bacteria with an interruption point from 16 μg/mL. The indicated dosing regimen did not meet the target PK/PD values in the case of resistant strains.